Application of Bevacizumab Combined With Chemotherapy in Patients With Colorectal Cancer and Its Effects on Brain-Gut Peptides, Intestinal Flora, and Oxidative Stress - Chen, Chao; Hou, Songtao; Zhao, Fei; Wu, Bin; Liu, Tingting; Zhang, Zhao; Li, Yuwei; Li, Hongchao (Frontiers in Surgery, 2022)
Objective: To investigate the efficacy of bevacizumab combined with chemotherapy in the treatment of colorectal cancer (CRC) and to analyze the effects on brain peptides, intestinal flora and oxidative stress in CRC patients. Methods: 82 patients with CRC who were admitted to our hospital from March 2018 to June 2021 were selected as the research subjects and divided into the control group (n=41) and the observation group (n=41). The control group was treated with XELOX chemotherapy, and the observation group was additionally treated with bevacizumab, which was repeated every three weeks for a total of two treatments. The therapeutic effects of the two groups were evaluated after treatment. The brain-gut peptide index, intestinal flora index and oxidative stress index were detected, and the adverse reactions of the two groups were recorded. Results: In the control group, ER was 36.59% (15/41) and DCR was 73.17% (30/41). In the observation group, ER was 63.41% (26/41) and DCR was 90.24% (37/41). ER and DCR in the observation group were higher than those in the control group (P<0.05). After treatment, the levels of motilin and gastrin in the observation group were lower than those in the control group, and ghrelin was higher than that in the control group (P<0.05). After treatment, the levels of Bifidobacterium, Lactobacilli and Enterococcus in the observation group were higher than those in the control group, and the level of Escherichia coli was lower than that in the control group (P<0.05). After treatment, the SOD level of the observation group was lower than that of the control group, and the MDA level was higher than that of the control group. Conclusion: Bevacizumab combined with chemotherapy has good efficacy in the treatment of colorectal cancer patients, which can effectively improve the gastrointestinal motility of patients, regulate the intestinal flora of the body, rebuild the microecological balance, effectively reduce the oxidative stress response of patients, and reduce the incidence of adverse reactions.